Integration of a Quantum Voting Scheme into Grayscale Images Using the Novel Enhanced Quantum Representation and Qiskit Framework - Alexandru-Gabriel Tudorache; Vasile Manta; Simona Caraiman (Modelling and Simulation in Engineering)
This paper illustrates the way a proposed quantum voting scheme can be designed in combination with a steganography technique called Least Significant Bit (LSB), by modifying a small number of pixels in multiple grayscale images. It combines the voting scheme with the novel enhanced quantum representation (NEQR) of an image, where the LSBs of these pixels represent the vote for each entity that takes part in the voting process. A server is also used, not only to count but also to guarantee the integrity of the votes (which is done inherently, by its design and quantum properties). The superdense coding circuit is part of the design, allowing each voter to use one qubit in order to transmit two classical bits (the vote value). The selected platform for testing this scheme is IBM Quantum Experience, together with the open-source framework called Qiskit (written in Python). This framework allows users to create various quantum circuits, using a wide selection of quantum gates, and then to simulate them, either on a simulator or on a real quantum device. The quantum circuits and the measurement results are also presented in this paper.